2022
DOI: 10.3390/su14010497
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the Impacts of a Prolonged COVID-19 Pandemic on the Sustainability of Culinary Tourism: Some Insights from Micro and Small Street Food Vendors

Abstract: Our study reveals the impacts of various COVID-19-related restrictions on the culinary tourism industry by exploring how street food vendors deal with this unprecedented encounter. The data were collected through semi-structured interviews of 20 street food vendors and later analyzed using qualitative data analysis, focusing on the thematic analysis of coded interview transcripts, as a basis for generalization of our findings. This study unfolds the knock-on effects of the lock-down, social distancing, and mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…GSC and innovation encourage employee competence in production and cost efficiency [45], thereby increasing added value and company profits [46]. If successful, the market share that can grow from the GSC agreement [47] and green product innovation can provide long-term benefits [48] by conducting research and developing new product diversification sustainably [49].…”
Section: H2: Green Strategic Consensus Has a Positive Effect On Agro-...mentioning
confidence: 99%
“…GSC and innovation encourage employee competence in production and cost efficiency [45], thereby increasing added value and company profits [46]. If successful, the market share that can grow from the GSC agreement [47] and green product innovation can provide long-term benefits [48] by conducting research and developing new product diversification sustainably [49].…”
Section: H2: Green Strategic Consensus Has a Positive Effect On Agro-...mentioning
confidence: 99%
“…The COVID-19 pandemic has undoubtedly provided a great stimulus for resilience related research in hospitality. Non-pharmaceutical interventions have impacted face-to-face services severely (Gaffar et al , 2022; Kim et al , 2022; Lopes et al , 2021). The most effective responses and coping strategies include fostering adaptive and creative leadership, humility and cautious navigating through a deep uncertainty, flexibility in building on the unknown, enhancing social capital, developing mutual respect and positive interconnectivity (Altshuler and Schmidt, 2021).…”
Section: Issues In Resilience Research In Hospitalitymentioning
confidence: 99%
“…Such studies highlight importance of research of the interrelationships between different industry systems in terms of supply chains (Mandal and Dubey, 2020;Mandal and Saravanan, 2019) and the role of IT on resilience (Mandal, 2019). Like the findings of Biggs et al (2012bBiggs et al ( , 2015, Gaffar et al (2022) argued that street vendors in Indonesia "equipped" themselves with resilient skills, including sensing, learning, integrating and coordinating capabilities that assist street food vendors during the pandemic. Usher et al (2020) found that size mediated the resilience ability of businesses in Virginia Beach, USA.…”
Section: Capabilitiesmentioning
confidence: 99%
“…These questions rise the need for research on the effects of such events, and the attitudes of those effected [ 29 ], namely entrepreneurs/business, tourists and residents. The impact of the perceived risks on travel behaviour and tourism decision making during and after the COVID-19 pandemic has already been identified in different studies by Fusté-Forné et al (2021) [ 23 ], Gaffar et al (2022) [ 25 ] and Matiza, 2020 [ 30 ].…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the COVID-19 pandemic had a much more significant impact on the global travel industry than the previous health crises because of a much greater geographical expansion, leading to the widespread implementation of travel bans and lockdowns affecting domestic travel [ 13 , 20 ], in general, and international travel, in particular. The pandemic has been acknowledged as an extreme outlier in terms of its implications for tourism [ 21 ], as it was and continues to be a challenge for the overall worldwide tourist activity, an unprecedented crisis for the tourism economy as a result of the immediate and immense shock it triggered [ 22 , 23 , 24 , 25 ], generating devastating effects for the tourism sector [ 26 ]. By the same token, the COVID-19 outbreak altered the tourism model worldwide [ 27 ] and has given rise to a new model of tourism governance [ 28 ], the shock being felt differently by entrepreneurs/businesses, tourists and residents.…”
Section: Introductionmentioning
confidence: 99%